2018
DOI: 10.3389/fnins.2018.00882
|View full text |Cite
|
Sign up to set email alerts
|

Ion Beam Assisted E-Beam Deposited TiN Microelectrodes—Applied to Neuronal Cell Culture Medium Evaluation

Abstract: Microelectrode material and cell culture medium have significant roles in the signal-to-noise ratio and cell well-being in in vitro electrophysiological studies. Here, we report an ion beam assisted e-beam deposition (IBAD) based process as an alternative titanium nitride (TiN) deposition method for sputtering in the fabrication of state-of-the-art TiN microelectrode arrays (MEAs). The effects of evaporation and nitrogen flow rates were evaluated while developing the IBAD TiN deposition process. Moreover, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Next, we used a multi-electrode array (MEA) system to analyze the effects of BrainPhys culturing on spontaneous activity. Although the neurons cultured in BrainPhys medium detached from the electrodes in MEA plates during long-term culturing, as was previously observed 39 , switching to BrainPhys for six to ten days was enough to increase both the number of spikes and the number of population bursts in mature neurons differentiated according to Shi et al 12 . Taken together, our findings are in line with earlier findings 15 and support the observation of increased neuronal networks and synaptic activity.…”
Section: Discussionmentioning
confidence: 59%
“…Next, we used a multi-electrode array (MEA) system to analyze the effects of BrainPhys culturing on spontaneous activity. Although the neurons cultured in BrainPhys medium detached from the electrodes in MEA plates during long-term culturing, as was previously observed 39 , switching to BrainPhys for six to ten days was enough to increase both the number of spikes and the number of population bursts in mature neurons differentiated according to Shi et al 12 . Taken together, our findings are in line with earlier findings 15 and support the observation of increased neuronal networks and synaptic activity.…”
Section: Discussionmentioning
confidence: 59%
“…Openings for the electrodes and the contact pads were dry etched with SF 6 + O 2 RIE process (Williams et al, 2003). Two MEAs of each ALD TiN thicknesses were fabricated, and for another of each thickness an additional 400 nm of TiN coating was deposited on the contact pads and large ground electrodes with IBAD technique (Ryynänen et al, 2018b) to enhance the mechanical durability.…”
Section: Methodsmentioning
confidence: 99%
“…Such small electrodes have rather high impedance and noise levels due to small contact area with the cells and culturing medium. In order to decrease noise and impedance, the active surface area of the electrode can be increased by using columnar or porous electrode materials like titanium nitride (TiN) (Egert et al, 1998; Ryynänen et al, 2018b) or platinum black (PtB) (Thomas et al, 1972; Pine, 1980; Oka et al, 1999). However, in addition to electrical measurements, it is often necessary to image and observe the cells growing or fixed on the MEA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sputter deposition is the standard method for depositing both ITO [21,22] and TiN [13] thin films. However, we have successfully shown that ion beam assisted electron beam deposition (IBAD) can also be used as a deposition method in fabrication of opaque TiN electrodes [23]. In this paper, IBAD TiN has been applied not only as an opaque layer, but also as a very thin transparent top layer for the ITO electrodes.…”
Section: Introductionmentioning
confidence: 99%